Clinical context and genetics of obesity. A complex world to elucidate - Jaramillo-Jaramillo, Laura Isabel (2017)
The World Health Organization defines obesity as the excessive fat accumulation that poses a risk to health; it represents a public health problem. Obesity is a complex disease that depends on numerous factors including the environment and diet. However, despite exposure to the same factors, some people develop more severe degrees of obesity than others, due to individual genetic predisposition.